A brief history of visualizing membrane systems in molecular dynamics simulations - Corey, R. A.; Baaden, M.; Chavent, M. (Frontiers in Bioinformatics, 2023)
Understanding lipid dynamics and function, from the level of single, isolated molecules to large assemblies, is more than ever an intensive area of research (Levental and Lyman, 2022). The interactions of lipids with other molecules, particularly membrane proteins, are now extensively studied. With advances in the development of force fields for molecular dynamics simulations (MD) and increases in computational resources, the creation of realistic and complex membrane systems is now common. This situation poses a major challenge for the analysis of these systems to make sense of what is perceived a priori as a sum of erratic movements and interactions.